A-284 A Systematic Review of Exercise for the Management of Post-Concussion Symptoms. (17th August 2022) - Jaganathan, Kannan Singaravelu; Sullivan, Karen; Kinmond, Sally; Berndt, Sara; Street, Steven; Haden, Catherine; Greenslade, Jaimi; McMahon, Katie; Mitchell, Gary; Kerr, Graham
Abstract: Objective: Exercise rehabilitation for post-concussion symptoms (PCS) has shown benefits, but a synthesis of evidence has been lacking. This systematic review aimed to review the evidence from randomised control trials (RCTs) of exercise-only interventions for PCS and identify the most promising parameters for further investigation. Data Selection: Electronic databases (CINAHL, EBSCOhost, MEDLINE, etc) and trial registries (ProQuest Dissertation & Theses Global Database, etc) were searched from inception to November 2020. Keyword searches was carried out using terms specifying "mild traumatic brain injury", "post-concussion symptoms", and "exercise". Only RCTs using solely exercise interventions and published in English were considered. Studies with multi-disciplinary interventions were excluded. Two independent researchers screened and reviewed the literature. Methodological quality was assessed using the Cochrane's Risk-of-Bias-2 tool. Eight studies were identified for the final review. Data Synthesis: The review found moderate support for exercise interventions to be effective in treating PCS. Based on the 8 studies, exercise programs that led to favourable outcomes commenced after an initial period of rest for 24-48 hours post-concussion, used progressive aerobic exercise for at least 4 times a week for 10-15 minutes during each session, required an intensity of at least 50% of the heart rate of the sub-symptom threshold, and lasted for at least 4 weeks or resolution of symptoms. Conclusions: Exercise rehabilitation for PCS may be beneficial but further research is required on wider population groups apart from adolescents and athletes before more generalised recommendations can be made.